‘No Cuts to Education’: The Story of a Protest Movement - Bocking, Paul (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
The return of the Conservatives to power in Ontario, Canada in 2018 saw major attacks on the province’s K-12 education system, centering on increases to class size and mandatory e-learning courses for students which, taken together with other budget cuts, amounted to the elimination of thousands of teaching and support staff positions, as well as threats of privatization. These policies provoked widespread resistance from education workers, who as union members and grassroots activists conducted extensive outreach to build public support, engaged in job actions, and participated in the largest strikes in Ontario for decades as part of the campaign for “No Cuts to Education.” The start of the COVID-19 pandemic in the spring of 2020 ended the movement. This article assesses the victories and defeats of this key struggle in defense of public education. It considers the strategies and tactics of provincial and local union leadership and activist members, in which the battle with the provincial government for the alignment of public support was widely recognized as being of decisive importance. The author uses autoethnographic research as a local union leader, interviews with active union members, policy documents, union statements and media coverage to construct an historical account. This experience has relevance for studies of teachers’ resistance to the neoliberalization of education, as well as social movement unionism and its challenges.